Nilai Moral dalam Novel Kawi Matin di Negeri Anjing Karya Arafat Nur - Wahid, Muhammad Arriza Nur; Sutejo, Sutejo; Suprayitno, Edy (STKIP PGRI Ponorogo Press, 2021)
This study aims to describe the representation of moral values in novel Kawi Matin di Negeri Anjing by Arafat Nur. The design used in this research was a literature review. The data source is the novel Kawi Matin di Negeri Anjing. Data collection techniques used were reading and note taking. The data were analyzed descriptively based on the sociology of literature theory. The results showed that the representation of moral values within the novel ere fortitude, oppression, mutual help, and compassion. The representation of fortitude was shown by the Kawi character in living life with all its shortcomings. The form of oppression was represented through the arrogant behavior of the army towards the citizens. The value of helping is represented through the behavior of the character of Kawi’s uncle who was willing to take care of the sick Kawi’s mother sincerely. The representation of the value of compassion could be seen from the character Kawi who still cared and loved Baidah even though she had been harassed by the army and finally gave birth to a child.